Coil placement after clipping: endovascular treatment of incompletely clipped cerebral aneurysms: Report of two cases - Forsting, Michael; Albert, Friedrich; Jansen, Olav; Kummer, Rüdiger von; Aschoff, Alfred; Kunze, Stefan; Sartor, Klaus (Journal of neurosurgery, 1996)
✓ In up to 4% of patients whose aneurysms are microsurgically clipped, there is an expected or unexpected aneurysm residuum. The authors describe two patients in whom surgical clipping did not result in complete obliteration of the aneurysm sac and in whom a second operation was not believed to be the solution to the problem. In both patients complete occlusion of the aneurysm residuum was achieved via an endovascular approach. Using the Guglielmi detachable coil system, it was possible to place two platinum coils selectively into the aneurysms. The endovascular approach may be a good treatment option for all patients in whom surgical clipping does not result in complete obliteration of the aneurysm sac and reoperation is contraindicated or unacceptable to the patient.